Communication medium: effects on affect, self-efficacy, and goals - Brunner, Jason (Kansas State University, 2008)
As organizations continue to decentralize, leaders will have to rely upon other forms of communication (e.g., telephone, video conferencing, email) to perform tasks normally done in face-to-face settings. Email is emerging as the most popular form of communication as a replacement for face-to-face communication. However, email is not entirely capable of conveying the same message as face-to-face interaction. Email is considered a lean form of communication due to the loss of non-verbal cues, the distance between the individuals, and time between messages. While email is a satisfactory replacement for some messages, research has yet to investigate its usefulness in providing performance feedback. As leaders begin to use email as a means of providing feedback, it is necessary to investigate the impact this form of communication has on the goals individuals set, self-efficacy, and affect. The study sampled 94 undergraduate students. The participants were randomly assigned to either receive positive or negative feedback via email or face-to-face interaction. Upon completion of the task, participants created goals to help them improve in the task and completed all other measures. Results indicate that it does not matter whether participants receive face-to-face or email feedback in respect to differences in their reported affect, efficacy, or the goals they set.
Keywords: Communication; Feedback; Psychology, Industrial (0624)